Valorisation of Beetroot Peel for the Development of Nutrient-Enriched Dehydrated Apple Snacks - Ioana Buțerchi; Liliana Ciurlă; Iuliana-Maria Enache; Antoanela Patraș; Gabriel-Ciprian Teliban; Liviu-Mihai Irimia (Foods)
Beetroot peel, an underutilised by-product of the food industry, has significant potential for valorisation due to its high content of bioactive compounds and natural pigments. This study aimed to sustainably reintroduce beetroot peel into the food chain by enriching the nutritional value of dehydrated apple snacks. Five experimental formulations of apple slices were developed: dipped in 5% RBPP in water, dipped in 10% RBPP in water, dipped in 5% RBPP in 50% lemon juice, dipped in 10% RBPP in 50% lemon juice all seasoned with cinnamon powder, and a control formulation. The biochemical analysis showed that the total phenolic content (2780.01 ± 68.38 mg GAE/100 g DM) and antioxidant activity of apple snacks significantly increased (503.96 ± 1.83 µmol TE/g DM). Sensory evaluation indicated that snacks with beetroot peel powder and lemon juice achieved the highest scores in colour, flavour, and acceptability. These results demonstrate that the valorisation of beetroot peel has the potential to reduce agro-industrial waste and also enhance the nutritional and functional quality of apple snacks. It is recommended that beetroot peel be further explored as a cost-effective natural ingredient to develop healthier, value-added snack products within a circular economy framework.